Superapp Byond: Technology Acceptance Mode (TAM) Analysis of Donation Decisions among BSI Customers in Malang City - Zihni, Muhammad Fazil; Laila, Faizzatin Nur; Fillah, Haidar Jihadi (JURNAL EKONOMI SYARIAH, 2025)
Introduction to The Problem: The launch of BSI Mobile and Superapp Byond mobile banking is a form of fintech adoption by BSI that also offers digital ZISWAF features. There has been a surge in digital infaq transactions through Byond BSI, reaching 15 million transactions throughout 2024–2025. This transformation raises questions about the factors influencing customers' decisions to use these infaq features, particularly in the context of adopting Islamic financial technology.Purpose/Objective of Study: This study aims to analyze the influence of perceived ease of use (PEOU) and perceived usefulness (PU) on customers' decisions to pay infaq through the Byond BSI Superapp in Malang City, using the Technology Acceptance Model (TAM).Design/Methodology/Approach: This study uses a quantitative approach with a logistic regression method. Data was collected through a questionnaire distributed to customers using the Byond BSI Superapp in Malang City and analyzed to determine the influence of the PEOU and PU variables on the decision to pay zakat digitally.Findings: Perceived ease of use (PEOU) and perceived usefulness (PU) have a positive, significant effect on the decision to donate. These findings confirm that the ease and usefulness of the Byond BSI Superapp are the main determinants in encouraging digital donation behavior among customers.Paper Type: Research Article